Mathematics Achievement of Ethnic Group Students: A Quantitative Study in Banke District - Adhikari, Ganesh Prasad (Academia Research Journal, 2022)
The study investigated the mathematics achievement of ethnic group students. The main objectives of this study were to seek mathematics Achievement of Tharu and Muslim ethnic groups on cognitive level: Knowledge, Skill, Comprehension and Application of grade nine students of Banke district. Achievement test was taken to get the required information. It was taken among 240 students on both ethnic group students. Two tailed t-test at 0.05 level of significance was used to analyze the collected data. The finding of this study shows that the Tharu ethnic group students were found to be significantly better in mathematics than the Muslim students on the Knowledge, Skill, and Comprehension. But there is no significant difference in the Application level in both groups of students.